American idol after Iraq : competing for hearts and minds in the global media age - Gardels, Nathan (Wiley-Blackwell, 2009)
This little book explores the role of US media in foreign policy, not only at the present moment, but with an eye to the future. Written by a veteran Hollywood film executive and an internationally known columnist in foreign affairs, it explains how American movies, TV shows, and pop music provide the images of America to the rest of the world, and the rest of the world to Americans; includes discussions of such issues as the cartoons of the Prophet Mohammed in Danish newspapers, Tibetan monks censored out of Chinese TV news reports only to show up on YouTube, and the Vatican's assault on the Da Vinci Code movie; and argues that Hollywood is a key player in the "deep coalition" required to support a "smart power" foreign policy and build a global cultural infrastructure that will make the world safe for interdependence.--From publisher description